Odpowiedzi

2010-01-04T23:49:15+01:00
A)2x-7-[5x²-3x-(2-4x+x²)]=
2x-7-[5x²-3x-2+4x-x²]=
2x-7-5x²+3x+2-4x+x²=
x-5-4x²

b)3-x²-[2-2x²-(3x²-2x+1)]=
3-x²-[2-2x²-3x²+2x-1]=
3-x²-2+2x²+3x²-2x+1=
2+4x²-2x

c)4x+3-[x-3x²-(6-3x-x²)]=
4x+3-[x-3x²-6+3x+x²]=
4x+3-x+3x²+6-3x-x²=
9+2x²

d)3x²-5x-[1-3x-(2+4x-x²)] =
3x²-5x-[1-3x-2-4x+x²]=
3x²-5x-1+3x+2+4x-x²=
2x²+2x+1
Najlepsza Odpowiedź!
2010-01-04T23:50:40+01:00
A)2x-7-[5x²-3x-(2-4x+x²)]=
2x-7-[5x²-3x-2+4x-x²]=
2x-7-5x²+3x+2-4x+x²=
x-5-4x²

b)3-x²-[2-2x²-(3x²-2x+1)]=
3-x²-[2-2x²-3x²+2x-1]=
3-x²-2+2x²+3x²-2x+1=
4x²-2x

c)4x+3-[x-3x²-(6-3x-x²)]=
4x+3-[x-3x²-6+3x+x²]=
4x+3-x+3x²+6-3x-x²=
9-2x²

d)3x²-5x-[1-3x-(2+4x-x²)] =
3x²-5x-[1-3x-2-4x+x²]=
3x²-5x-1+3x+2+4x-x²=
2x²=2x+1